2010
DOI: 10.1002/btpr.525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenolic monomers on growth of Acidothermus cellulolyticus

Abstract: Previous studies on biological pretreatment of switchgrass by solid-state fermentation with Acidothermus cellulolyticus 11B have shown that inhibitory compounds prevent growth on untreated switchgrass. A. cellulolyticus was grown in liquid medium containing cellobiose with phenolic monomers added to determine if the phenolic compounds are one possible source of inhibition. Cinnamic acid derivatives (trans-p-coumaric, trans-ferulic, and hydrocinnamic acids), hydroxybenzoic acids (p-hydroxybenzoic, syringic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Additional literature discusses inhibition by products formed during biomass pretreatment [4,5,40-43]. Many of the non-carbohydrate compounds are believed to be inhibitory in nature [42,44-47]. …”
Section: Resultsmentioning
confidence: 99%
“…Additional literature discusses inhibition by products formed during biomass pretreatment [4,5,40-43]. Many of the non-carbohydrate compounds are believed to be inhibitory in nature [42,44-47]. …”
Section: Resultsmentioning
confidence: 99%
“…Possible inhibitory compounds include phenolic compounds, which are a byproduct of lignin degradation (Almeida et al, 2007; Palmqvist and Hahn‐Hagerdal, 2000). Lignin has been shown to decrease growth and enzyme activity in Trichoderma reesei (Vohra et al, 1980) and lignin‐derived compounds have been shown to inhibit cellulases and xylanases produced by thermophilic bacteria (Joh et al, 2011; Ximenes et al, 2010). To prevent inhibition in future adaptation studies, enriched samples could be leached prior to inoculating subsequent batches of feedstock.…”
Section: Discussionmentioning
confidence: 99%